Risk factors for neonatal sepsis among neonates in the neonatal intensive care unit at Hawassa University Comprehensive Specialized Hospital and Adare General Hospital in Hawassa City, Ethiopia - Shifera, Nigusie; Dejenie, Filagot; Mesafint, Gebremeskel; Yosef, Tewodros (Frontiers in Pediatrics, 2023)
Background: Neonatal sepsis (NS) is a serious blood bacterial infection at the age of less than or equal to 28 days, which is manifested by systemic signs, and symptoms of infection. It is one of the leading causes of admission and death in developing countries like Ethiopia. Understanding different risk factors for neonatal sepsis is essential for early diagnosis and treatment of the disease. So this study aimed to assess the risk factors of neonatal sepsis among neonates at Hawassa University Comprehensive Specialized Hospital and Adare General Hospital in Hawassa city, Ethiopia. Methods and Materials: A case-control study design was employed on 264 neonates (66 cases and 198 controls) in Hawassa University Comprehensive Specialized Hospital and Adare General Hospital from April to June/2018. Data were collected by interviewing the mothers and reviewing neonates’ medical records. The data were edited, cleaned, coded, and entered into Epi info version 7, and were transported and analyzed using SPSS version 20. The odds ratios (ORs) with 95% confidence intervals (CIs) were used to assess the significance of the associations. Result: A total of 264 neonates (66 cases and 198 controls) with a hundred percent of response rate. The mean (±SD) age of mothers was 26 ±4.042 years. The majority 84.8% of the cases were found under the age of seven days with a mean age of 3.32 days ±3.376 SD. Factors prolonged rupture of the membrane [AOR =4.627; 95% CI (1.997-10.72)], history of the urinary tract or sexually transmitted infections [AOR = 2.5; 95% CI (1.151-5.726)], intrapartum fever [AOR =3.481; 95% CI (1.18-10.21)], foul smelling liquor [AOR =3.64; 95% CI (1.034-12.86)], and low APGAR score in the 5th minute [AOR = 3.38; 95% CI (1.107-10.31)] were the independent predictors of neonatal sepsis.